A Hubungan Lama Bekerja dan IMT dengan Low Back Pain Pada Pengemudi Taksi X Pekanbaru - Yuharika Pratiwi, Rika; Waren, Annes; Akbar, Romi (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2020)
Work-related LBP is pain from the lower back that is related to work which can be clinically caused or exacerbated by work. Based on the initial survey, it is found that 70% of X taxi drivers experienced LBP. This study aims to determine the factors associated with LBP in taxi drivers X. This type of quantitative observational research, cross-sectional study design with a sample of 43 respondents. Data analysis used univariate, chi-square used bivariate analysis. Based on the results of the chi-square test, it showed that the variables associated with LBP were the length of work (p-value = 0.008). The variables not related to LBP was Body Mass Index (p-value = 0.348). Keywords: low back pain, taxi driver